An Analysis on Indonesian—English Abstract Translation to Enhance Multicultural Language in Accounting Department, State Polytechnic of Malang - Fitrotul Maulidiyah (Jurnal Ijtihad, 2023)
Thesis writing is one compulsory subject which must be completed by students at State Polytechnic of Malang particularly in Accounting Department. Moreover, an abstract is an inseparable part of thesis which must be written by all students. The abstracts must be written both in Indonesian and English. Students have to translate their Indonesian abstract into English. From the preliminary study, it was found out that students have many difficulties in translating their thesis abstract from Indonesian into English. Hence, this research seeks to investigate what type of errors committed by the students during the process of English abstract writing. A descriptive qualitative design was used in this research. Documents in the form of 25 abstracts were used in the data analysis. The results showed that during the process of English abstract writing completion, students tend to have problems in abstract translation, grammar, vocabularies, sentence structures and writing mechanics. Detailed results were presented and discussed in the coming sections, followed by recommendations for further research. Keywords: abstract writing, translation, machine translation, Google Translate